Characterization of the Arabidopsis Adh G-box binding factor. - DeLisle, A J (1990)
Protein-DNA interaction at an inverted repeat of the sequence 5'-GTGG-3' (G-box) has been associated with the transcription of several plant genes [Giuliano, G., et al. (1988). Proc. Natl. Acad. Sci. USA 85, 7089-7093; Ferl, R.J., and Laughner, B.H. (1989). Plant Mol. Biol. 12, 357-366; Schulze-Lefert, P., et al. (1989). EMBO J. 8, 651-656]. We characterized the binding of the Arabidopsis G-box binding factor (GBF) from whole-cell extracts and fractionated extracts to the G-box of alcohol dehydrogenase (Adh) using gel mobility shift assays. DNase I footprinting localized the region of GBF/G-box interaction to two sites, one apparent high-affinity binding site (-227 to -201) and a possible low-affinity binding site (-193 to -182). DNA-protein cross-linking demonstrated that the G-box is bound by proteins of two sizes, 31 kilodaltons and 18 kilodaltons. In addition, we found that in vitro the interaction of GBF from Arabidopsis suspension cultures or leaves with the Adh G-box is indistinguishable, and that there is evidence of multiple protein-protein interactions.